Development through debt: Rationalizing the costs of external borrowing - Enamidem U. Ubok-Udom (Intereconomics, 1979)
Mounting external indebtedness has become a major problem for many developing countries. This may be not least a result of the fact that economists and policy-makers have tended to emphasize the benefits to the recipient countries of external borrowing to the neglect of its costs.
Keywords: 330; Capital Transfer